2016
DOI: 10.18632/oncotarget.13891
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Snail and NF-κB predicts poor survival in Chinese hepatocellular carcinoma patients

Abstract: In this study, we explored the roles of Snail and NF-κB in hepatocellular carcinoma (HCC). Samples of HCC tumor tissue were collected from 83 Chinese HCC patients. Snail and NF-κB expression was then examined based on immunohistochemical staining, and the relations between Snail and NF-κB expression and the clinical characteristics of the patients were assessed using Cox model analysis. Snail and NF-κB were both expressed in HCC tissue, and their levels were strongly correlated. In addition, levels of both Sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The zinc-finger transcriptional repressor Snail reportedly contributes to EMT in HCC and plays a key role in tumorigenesis, differentiation, migration and invasiveness ( 31 ). In addition, recent research has revealed that Snail expression is negatively related to tumor differentiation, which is an independent factor predictive of survival in HCC patients ( 32 ). Loss of E-cadherin and gain of vimentin are known to play key roles in the EMT process of various human types of cancer, including HCC ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The zinc-finger transcriptional repressor Snail reportedly contributes to EMT in HCC and plays a key role in tumorigenesis, differentiation, migration and invasiveness ( 31 ). In addition, recent research has revealed that Snail expression is negatively related to tumor differentiation, which is an independent factor predictive of survival in HCC patients ( 32 ). Loss of E-cadherin and gain of vimentin are known to play key roles in the EMT process of various human types of cancer, including HCC ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is considerable controversy regarding the role of NF-κB in the development of HCC, as several studies also reported induction of pro-tumorigenic features upon NF-κB inactivation [15,47,55,56]. Nonetheless, it is indisputable that NF-κB can play a direct or indirect role in hepatocarcinogenesis, and that dysregulation can considerably influence clinical outcome [14,57,58].…”
Section: Nf-κb In Hepatocarcinogenesismentioning
confidence: 99%
“…Snail recruits the histone demethylase lysine-specific demethylase 1 (LSD1), which removes the dimethylation of K4 on histone H3 (H2K4m2) and mediates the transcriptional repression of CDH1 [126]. Elevated Snail levels predict the poor survival of HCC patients [127].…”
Section: Clinical Application Of Epigenetic Alterations As Hepaticmentioning
confidence: 99%